BANKING DISPUTE SETTLEMENT THROUGH ALTERNATIVE DISPUTE RESOLUTION: CLAIMS OF DANAMON BANK CUSTOMERS - Hartantin, Sinarianda Kurnia (jfpublisher, 2022)
The development of banking business in Indonesia is managed by several parties, namely the banking sector itself which has a role as business actor and creditor in relation to its role in providing banking services to the public and other parties are debtors, namely consumers (customers) or users of banking services. However, in practice, both of them are often involved in disputes. Seeing these conditions, alternative efforts are needed in resolving disputes ADR (Alternative Dispute Resolution). The purpose of this research is to increase the author's knowledge and ability in analyzing banking dispute resolution rules and increase the author's knowledge and ability in analyzing ADR legal problems according to Law No. 30/1999 concerning on the Arbitration and Alternative Dispute Resolution. The results of this study indicate that settlement of banking disputes through Alternative Dispute Resolution (ADR) according to Law no. 30 of 1999 can be known from banking disputes, the factors that cause banking disputes and the legal basis for the settlement of banking disputes through Alternative Dispute Resolution (ADR). Additionally, it is known that banking dispute resolution procedures through Alternative Dispute Resolution (ADR) according to Law No. 30/1999 consists of the pre-mediation stage, the mediation stage and the mediation outcome stage.